Generation paths of major production safety accidents — A fuzzy-set qualitative comparative analysis based on Chinese data - Zhou, Fujun; Zhang, Jian; Fu, Cheng (Frontiers in Public Health, 2023)
Major production safety accidents have become the key obstacle to improve the overall safety production level. Analyzing the causal relationship of major production safety accidents is helpful to clarify its characteristics and laws. Based on the literature, the analytical framework of "individual - technology - management - environment" is proposed. Taking 37 production safety accidents as samples, fuzzy set qualitative comparative analysis (fsQCA) is used to analyze the occurrence path and mechanism of major production safety accidents. The results show that: (1) Major production safety accidents are the result of multiple factors coupling. Minor external supervision or abnormal production behaviors are more likely to cause major production safety accidents. (2) When the production behavior is abnormal and the safety management ability is insufficient, major production safety accidents are more likely to occur. (3) There are five ways and three mechanisms for major production safety accidents. This work enriches the cognition of causality of production safety accidents from the perspective of configuration, clearly shows which variable combinations lead to major accidents, and helps to prevent and reduce major production safety accidents and their risks.